Oracle BPM suite 11g developer's cookbook : over 80 advanced recipes to develop rich interactive business processes using the Oracle Business Process Management suite - Acharya, Vivek (Professional expertise distilled., 2012)
This book is written in simple, easy to understand format with lots of screenshots and step-by-step explanations. If you are a BPM developer, looking to develop robust BPM solutions without impediments, then this is the best guide for you. This book assumes that you have a fundamental knowledge of BPM.